Sistem Hirarki Kelembagaan Badan Pengelola Zakat di Indonesia (Tinjauan Terhadap Pelaksanaan Undang-undang No. 23 Tahun 2011) - Mufidah Mufidah (Jurnal Cita Hukum, 2016)
Abstract: Government support for the existence and role of zakat management organization indicated by the issuance of legislation on the management of zakat that Act No. 38 of 1999 and the decision of the Minister of Religion No. 581 of 1999 on the implementation of Act No. 38 of 1999 which was amended by Act No. 23 of 2011 concerning the management of zakat. Many  factors of causing non-optimal zakat as legislation, mostly related to the system and institutional factors. In this case, should the government as well as amil zakat organization has a strategic role to establish an institutional system of zakat and charity empowerment and support the establishment of the implementation of the charity as a binding regulation. This can occur if the control system of zakat management organization operating effectively, as well as the existence of legislation on the management of zakat either No. 38 of 1999 and No. 23 of 2011. In other words, the optimization of the implementation of zakat is affected by the system and the effective management of zakat management in addition to firmness of government in enforcing the implementation of zakat either written in the legislation and are implementable in order to achieve good governance zakat (alms good governance).   Abstrak: Dukungan pemerintah terhadap keberadaan dan peran organisasi pengelola zakat ditunjukkan dengan dikeluarkannya peraturan perundang-undangan tentang pengelolaan zakat yaitu Undang-undang Nomor 38 Tahun 1999 dan keputusan Menteri Agama No. 581 Tahun 1999 tentang Pelaksanaan undang-undang Nomor 38 Tahun 1999 yang kemudian diperbaharui dengan Undang-undang Nomor 23 tahun 2011 Tentang pengelolaan zakat. Beberapa faktor penyebab belum optimalnya zakat sebagai peraturan perundang-undangan, sebagian besar terkait dengan faktor sistem dan kelembagaan. Dalam hal ini, seharusnya pemerintah serta organisasi pengelola zakat sebagai amil memiliki peran yang sangat strategis untuk membangun sistem kelembagaan zakat serta pemberdayaan zakat dan mendukung tegaknya pelaksanaan zakat sebagai peraturan yang mengikat. Hal ini dapat terjadi jika sistem pengendalian organisasi pengelolaan zakat berjalan dengan efektif, begitu juga keberadaan Undang-undang tentang pengelolaan zakat baik Nomor 38 Tahun 1999 maupun Nomor 23 Tahun 2011 . Dengan kata lain optimalisasi pelaksanaan zakat dipengaruhi oleh sistem dan manajemen pengelolaan zakat yang efektif disamping ketegasan pemerintah dalam menegakkan pelaksanaan zakat baik yang ditulis dalam peraturan perundang-undangan maupun secara implementatif demi terwujudnya tata kelola zakat yang baik (good zakat governance).   DOI: 10.15408/jch.v4i2.3673